(untitled) (Metakognisi, 2025)
Leadership models in education have an important role in determining the direction and quality of the learning process and institutional management. The three main models of leadership that are often discussed are democratic, laissez-faire, and authoritarian leadership. Democratic leadership emphasizes the active participation of all members of the organization, both educators and students, in decision making, thereby creating an inclusive and collaborative atmosphere. This model is believed to increase individual motivation, creativity and sense of responsibility. In contrast, laissez-faire leadership gives individuals complete freedom to act without much intervention from the leader. Although this model can encourage innovation for highly competent individuals, a lack of direction can lead to chaos or unclear organizational goals. Meanwhile, authoritarian leadership focuses on complete control by the leader, with clear instructions and strict discipline. This model is effective in situations that require quick and organized action, but can limit members’ freedom of thought and participation. This research aims to analyze the advantages, disadvantages and impacts of implementing each leadership model in an educational context, in order to provide insight into the development of effective and adaptive leadership in the modern educational environment. Keywords: Democratic, Laissez Faire and Authoritarian Leadership